New reconstruction of DAN5 cranium (Gona, Ethiopia) supports complex emergence of Homo erectus - Baab, Karen; Kaifu, Yousuke; Freidline, Sarah; Rogers, Michael; Semaw, Sileshi (Nature Communications, 2025)
The African Early Pleistocene is a time of evolutionary change and techno-behavioral innovation in human prehistory that sees the advent of our own genus, Homo, from earlier australopithecine ancestors by 2.8-2.3 million years ago. This was followed by the origin and dispersal of Homo erectus sensu lato across Africa and Eurasia between ~ 2.0 and 1.1 Ma and the emergence of both large-brained (e.g., Bodo, Kabwe) and small-brained (e.g., H. naledi) lineages in the Middle Pleistocene of Africa. Here we present a newly reconstructed face of the DAN5/P1 cranium from Gona, Ethiopia (1.6-1.5 Ma) that, in conjunction with the cranial vault, is a mostly complete Early Pleistocene Homo cranium from the Horn of Africa. Morphometric analyses demonstrate a combination of H. erectus-like cranial traits and basal Homo-like facial and dental features combined with a small brain size in DAN5/P1. The presence of such a morphological mosaic contemporaneous with or postdating the emergence of the indisputable H. erectus craniodental complex around 1.6 Ma implies an intricate evolutionary transition from early Homo to H. erectus. This finding also supports a long persistence of small-brained, plesiomorphic Homo group(s) alongside other Homo groups that experienced continued encephalization through the Early to Middle Pleistocene of Africa. The origin and dispersal of Homo erectus, a long-lived and geographically widespread human ancestor, are unclear despite a rich fossil record. Here, the authors reconstruct the face from a Homo erectus cranium from Gona, Ethiopia, dated to 1.5-1.6 million years ago, providing insights into the evolutionary transition from early Homo to H. erectus.
Keywords: Crania; Early Pleistocene; Hominidae; Homo erectus; Human evolution; Pleistocene; Sensu; Skull; dept.ant

Imposed Form in the Early Acheulean? Evidence from Gona, Afar, Ethiopia - Stout, Dietrich; Liu, Cheng; Muller, Antoine; Rogers, Michael; Semaw, Sileshi (Journal of Archaeological Method and Theory, 2025)
Keywords: Acheulean; Ancient history; Anthropology; Archaeology; Early Stone Age; Ethnology; Geography; Handaxe; History; Large cutting tool; Lithic technology; Pick; Pleistocene; Shaping; Sociology; dept.ant

Seeking Transcendence: The Quest for Spirituality in an Age of Detachment - Manzella, Joseph C. (Routledge, 2025)
Seeking Transcendence examines the various paths taken by those who have detached themselves from their traditional, institutional religious roots but are seeking non-traditional paths to spiritual experiences. Called the “nones” or "non-affiliated" in popular mass media, these include a significant number of Western folks who maintain a belief in God or at least consider themselves “spiritual but not religious”. Each chapter of the book explores these trends with a specific theme, as well as a case study based on the author’s ethnographic observation of alternative spiritual communities and practices in North America and Western Europe. Ultimately, this book shows how contemporary alternatives to traditional institutional religion appeal to nones, presenting the relevance of new religious movements and more secular spiritual paths to transcendence.
Keywords: Philosophy; Psychoanalysis; Psychology; Theology; Transcendence (philosophy); dept.ant

Long-term hominin preference for the gallery forest edge: Insights from the Gona paleosols, Afar, Ethiopia - Stinchcomb, Gary E.; Rogers, Michael J.; Semaw, Sileshi (Quaternary Science Reviews, 2025)
The Gona Paleoanthropological Research Project area in the Afar Region of Ethiopia arguably contains one of the most complete records of archaeological sites anywhere in the world, from the earliest Oldowan dated to 2.6 Ma, to the Later Stone Age (LSA) dated to ca. 12-7 Ka. This makes Gona an ideal place to examine long-term trends in hominin-environment interaction. We revisited archaeological and hominin fossil sites at Gona and characterized the fossil soils using paleopedology and found evidence of paleo-Fluvisols, -Cambisols and -Vertisols. Greater than 70% of those archaeological sites spanning Oldowan to the Later Stone Age are found in buried paleosols with A-C and A-Bk-C paleosol profiles resembling modern-day Fluvisols or Fluvic Cambisols. Fluvisol morphology shows presence of bedding, incipient soil structure development and overprinting after burial. Stratigraphy and lithofacies show that these paleo-Fluvisols were proximal to the ancestral Awash River (Type I depositional system) or a distal fan channel (Type II depositional system). These data suggest that soil burial rates were rapid due to proximal flooding, where this would be a primary factor inhibiting soil development. This style of sedimentation and weathering resembles a narrow (5–10 m width) strip of land in a modern-day channel shelf and bar setting, separating the river from the adjacent gallery forest. A review of the literature shows that the frequent association of artifacts with paleo-Fluvisols may be prevalent throughout eastern Africa and indicates a long history of hominin reliance on a riverine ecosystem edge, proximal stream water and gallery forest resources within broader river valleys. The few older archaeological sites (e.g., Oldowan and Acheulian) found in/on more well-developed paleosols at Gona are an exception to this rule. These latter sites may hint at different land-use patterns and thus differing trajectories of hominin-environmental interactions. Because most paleosol studies at Gona and elsewhere in eastern Africa use paleo-Vertisols or other more well-developed calcareous soils to reconstruct paleoenvironment, there is a potential spatial and temporal decoupling between those well-studied paleosols and the more weakly-developed ones where archaeology is found.
Keywords: Archaeology; Artificial intelligence; Astronomy; Computer science; Enhanced Data Rates for GSM Evolution; Geography; Geology; Gona; Mathematics; Paleoecology; Paleontology; Paleosol; Physics; Preference; River corridors; Statistics; Term (time); dept.ant; peer-reviewed

Gona, Ethiopia: microcosm of the stone age - Rogers, Michael J.; Semaw, Sileshi; Stinchcomb, Gary E.; Quade, Jay; Levin, Naomi E.; Cauche, Dominique (Handbook of Pleistocene Archaeology of Afric, 2023)
The Gona paleoanthropological field project in the Afar region of Ethiopia has long been associated with the earliest Oldowan stone tools. However, over the last 20 years, ongoing research at Gona has expanded its contributions considerably, producing fossils of Ardipithecus kadabba, Ardipithecus ramidus, and Homo erectus, as well as additional archaeological evidence of the earliest Oldowan and early Acheulean. Moreover, in the last few years, the Gona team has turned its attention to the younger deposits exposed in its study area and discovered a surprising number of Middle Stone Age (MSA) and Later Stone Age (LSA) archaeological sites, mostly from the Late Pleistocene to the early-middle Holocene. While any sedimentary sequence is incomplete by virtue of episodic depositional and erosional events over time, we are struck by the relative completeness of the archaeological sequence at Gona (Quade et al., 2008). The hominin fossils attract deserved attention, but the Gona project may ultimately be best known for preserving arguably the most extensive, detailed, and continuous Stone Age or Paleolithic archaeological sequence in the world, all contained within a small 25 km × 10 km area, approximately half of the total project area.
Keywords: dept.ant

Language and racial capitalism: linguistic anthropological approaches to minoritized labor, standard language, and racial bias - McGill, Kenneth (Transforming Anthropology, 2023)
This article examines racial capitalism from a semiotic perspective, arguing that economic value, like language and race, can be described in situated and indexical terms. I attempt to show how raciolinguistic bias in and around the workplace is linked to a larger labor market in which minoritized labor is reproduced in a systemic way, and to explore hegemonic formations of racialization in the workplace and beyond. The jumping-off point for much of my argument is the work of the historian and political theorist Cedric Robinson.
Keywords: dept.ant; labor; language; markets; minoritization; peer-reviewed; race

A Culture of News. - Manzella, Joseph (2000)
Keywords: dept.ant; faculty_collection; sabbatical_report

Results of an Analysis of Carnivore Tooth Mark Shape. - Selvaggio, Marie (2000)
Keywords: dept.ant; faculty_collection; sabbatical_report

The Wari Civilization and Their Descendants: Imperial Transformation in Pre-Inca Cuzco - Glowacki, Mary; McEwan, Gordon Francis (Lexington Books, 2021)
"Drawing on research conducted in Cuzco, Peru, The Wari Civilization and Their Descendants: Imperial Transformation in Pre-Inca Cuzco analyzes the political and social transformations that led to the downfall of the Wari civilization in the Andean Middle Horizon period (AD 500-1000) and resulted in the rise of the Inca state."--
Keywords: Antiquities; Antiquities; Excavations (Archaeology); Cusco (Region); Indians of South America; Cusco (Region); Pikillacta Site (Peru); Cusco (Peru : Region); Cuzco; History; Huari pottery; Huari Indians; Peru; Politics and government; Huari Indians; dept.ant; faculty_collection

Global inequality - McGill, Kenneth (University of Toronto Press, 2016)
"Inequality is currently gaining considerable attention in academic, policy, and media circles. From Thomas Piketty to Robert Putnam, there is no shortage of economic, sociological, or political analyses. But what does anthropology, with its focus on the qualitative character of relationships between people, have to offer? Drawing on current scholarship and illustrative ethnographic case studies, McGill argues that anthropology is particularly well suited to interrogating global inequality, not just within nations, but across nations as well. The book is designed to be used flexibly in a variety of undergraduate classes--from introductory cultural anthropology, to courses on globalization, economic and political anthropology, and inequality. Brief, accessibly written, and peppered with vivid ethnographic examples that bring contemporary research to life, Global Inequality is a unique offering for undergraduate anthropology courses."--
Keywords: Case studies; Equality; Ethnology; dept.ant; faculty_collection

Everyday Ethnicity in Sri Lanka: Up-Country Tamil Identity Politics - Bass, Daniel (Routledge contemporary South Asia series, 2013)
Focusing on notions of diaspora, identity and agency, this book examines ethnicity in war-torn Sri Lanka. It highlights the historical development and negotiation of a new identification of Up-country Tamil amidst Sri Lanka's violent ethnic politics. Over the past thirty years, Up-country (Indian) Tamils generally have tried to secure their vision of living within a multi-ethnic Sri Lanka, not within Tamil Eelam, the separatist dream that ended with the civil war in 2009. Exploring Sri Lanka within the deep history of colonial-era South Asian plantation diasporas, the book arg
Keywords: 1978-; Ethnic identity; Malaiyaha Tamil (Sri Lankan people); Government policy; Malaiyaha Tamil (Sri Lankan people); Political aspects; Sri Lanka; Politics and government; Politics and government; Sri Lanka; Race relations; Sri Lanka; Tamil diaspora; Malaiyaha Tamil (Sri Lankan people); dept.ant; faculty_collection

Stone Tool Variability and the Ecological Context of the Earliest Archaeological Record - Rogers, Michael J. (2013)
Keywords: dept.ant; faculty_collection; sabbatical_report

Anthropological and ethnographic approach to breastfeeding. - Skoczen, Kathleen Nora (2012)
Dr. Skoczen continued research on bio-cultural and historical factors in breastfeeding, including ethnographic, in-depth interviews with new mothers, observing workshops, participation in conferences, and working on a manuscript devoted to this subject. She also worked on enhancing several of her classes and preparing a new course on cultural ecology.
Keywords: dept.ant; faculty_collection; sabbatical_report

Common Purse, Uncommon Future the Long, Strange Trip of Communes and Other Intentional Communities - Manzella, Joseph C. (Praeger, 2010)
Common Purse, Uncommon Future: The Long, Strange Trip of Communes and Other Intentional Communities explores the many new types of communal living being tried in America and Europe today. A growing number of people disenchanted with the pressures and demands of mainstream lifestyles are drawn by the nostalgic appeal of traditional, mostly agrarian and artisanal, lifestyles as practiced in residential communities where liminal rituals of membership serve to validate pacts to live and work together in cooperative social and economic relations.
Keywords: Collective settlements; History; History; Communitarianism; United States; dept.ant; faculty_collection

The Struggle to Revitalize American Newspapers - Manzella, Joseph C. (Mellen studies in journalism ; v. 2, 2002)
Keywords: 20th century; Journalism; 20th century; Newspaper publishing; American newspapers; History; United States; dept.ant; faculty_collection

Fluvial response to Quaternary hydroclimate in eastern Africa: Evidence from Gona, Afar, Ethiopia - Stinchcomb, Gary E.; Quade, Jay; Levin, Naomi E.; Iverson, Nels; Dunbar, Nelia; McIntosh, William; Arnold, Lee J.; Demuro, Martina; Duval, Mathieu; Grün, Rainer; Zhao, Jian-xin; White, Marie; et al. (Quaternary Science Reviews, 2023)
The Busidima Formation in the Afar region, Ethiopia, spans the Quaternary and records the cultural evolution of the genus Homo. Yet, the Middle Pleistocene to Holocene fluvial environments in which early humans lived are undersampled in eastern Africa. This paper examines the stratigraphy, geochronology and paleoenvironments of the newly designated Odele Member of the uppermost Busidima Formation (<152 thousand years ago (ka)), which has received little attention despite representing a critical period in the evolution of early Homo sapiens and its migration out of Africa. The Odele Member is 40–50 m thick and is dated using tephrochronology, radiometric, luminescence, and electron spin resonance techniques. The member spans 151 to 7 ka, defined at the base by the widespread Waidedo Vitric Tuff (WAVT, 151 ± 16 ka modeled age and 95.4% credible interval - C.I.). There are two prominent erosional unconformities in the Odele Member, a lower one after the WAVT deposition with a modeled 95.4% C.I. range of 124–97 ka; and an upper one involving widespread alluvial fan incision commencing between 21.7 and 12.9 ka. The uppermost Odele Member also contains black, organic-rich mats, redox features, reed casts, and freshwater gastropods marking wetter conditions during the terminal Pleistocene and Early Holocene. A black, fine-grained relict soil coeval with the Halalalee paleosol bounds the top of the Odele Member and has mollic and vertic properties, weathering since ∼12 ka. These incision events and prominent paleosol development near/at the top of the Busidima Formation document Middle to Late Pleistocene Awash River incision to its present-day course. Paleo-rainfall estimates suggest that the Early Holocene-age Halalalee paleosol weathered under a climate with mean annual rainfall 10–15% higher than today. A compilation of radiocarbon ages from aquatic gastropods, carbonized wood and charcoal from the upper Odele Member shows wetter and possibly more vegetated conditions during late marine isotope stage (MIS) 3 and the African Humid Period (AHP) that are tightly coupled with precession-driven summer insolation maxima. These key findings suggest that periods of incision, aggregation, and landscape stability in the Odele Member have an orbital precession pacing. The Odele Member revises upward the age of the Busidima Formation to 7 ka, showing that it spans into the Holocene and now includes Middle and Later Stone Age archaeological traditions.
Keywords: Electron spin resonance; Ethiopian rift; Fluvial aggradation; Fluvial incision; Paleosol; Radiocarbon; Tephrochronology; U-series; dept.ant; pIR-IRSL; peer-reviewed

The endocast from Dana Aoule North (DAN5/P1): A 1.5 million year-old human braincase from Gona, Afar, Ethiopia - Bruner, Emiliano; Holloway, Ralph; Baab, Karen L.; Rogers, Michael J.; Semaw, Sileshi (American Journal of Biological Anthropology, 2023)
The nearly complete cranium DAN5/P1 was found at Gona (Afar, Ethiopia), dated to 1.5–1.6 Ma, and assigned to the species Homo erectus. Its size is, nonetheless, particularly small for the known range of variation of this taxon, and the cranial capacity has been estimated as 598 cc. In this study, we analyzed a reconstruction of its endocranial cast, to investigate its paleoneurological features. The main anatomical traits of the endocast were described, and its morphology was compared with other fossil and modern human samples. The endocast shows most of the traits associated with less encephalized human taxa, like narrow frontal lobes and a simple meningeal vascular network with posterior parietal branches. The parietal region is relatively tall and rounded, although not especially large. Based on our set of measures, the general endocranial proportions are within the range of fossils included in the species Homo habilis or in the genus Australopithecus. Similarities with the genus Homo include a more posterior position of the frontal lobe relative to the cranial bones, and the general endocranial length and width when size is taken into account. This new specimen extends the known brain size variability of Homo ergaster/erectus, while suggesting that differences in gross brain proportions among early human species, or even between early humans and australopiths, were absent or subtle.
Keywords: Homo erectus; Homo ergaster; Lower Pleistocene; brain evolution; dept.ant; human evolution; paleoneurology; peer-reviewed

The discursive malleability of an identity: A dialogic approach to language "medium" schooling in North India - LaDousa, C. (Journal of Linguistic Anthropology, 2006)
This article employs a dialogic approach, in the parlance of Bakhtin, to explore the ways in which a school's "medium," its primary language of instruction, has become a major category of identity in North India. Many people describe themselves and others by invoking attendance at either a Hindi- or English-medium school. The first task of this article is to account for what Bakhtin calls "centripetal forces" that enable people at different positions in terms of class or school experience to use a common duality of Hindiversus English-medium and its attendant social resonances. The second task is to account for the abilities of a teacher to question the inevitability of the medium divide and to radically reframe what is important about schooling. Her abilities derive, in part, from her experiences with schools, attesting to Bakhtin's insight that centripetal forces in language are never total, and that centrifugal forces arise from complex engagements with institutions. © 2006 by the American Anthropological Association. All rights reserved.
Keywords: dept.ant

Strontium isotope evidence for prehistoric migration at Chokepukio, Valley of Cuzco, Peru - Andrushko, V.A.; Buzon, M.R.; Simonetti, A.; Creaser, R.A. (Latin American Antiquity, 2009)
Although Spanish chroniclers referred frequently to coerced migration in the Inca Empire, these migrations have been difficult to document archaeologically. One approach to migration studies, strontium isotope (87Sr/86Sr) analysis, has emerged as an effective technique. Until now, however, this method has not been applied to the Inca heartland region of Cuzco, Peru. In this study, we use strontium isotope analysis to examine patterns of prehistoric migration in the Cuzco Valley. Human dental enamel samples from the Cuzco Valley site of Chokepukio are analyzed and compared to the local 87Sr/86Sr signature established through faunal specimens. Though tentative due to a small sample size, the isotope results do not provide evidence for migration at this site from the time periods preceding the rise of the Inca Empire (200 B.C. to A.D. 1400). In contrast, there is substantial evidence for migration during the time of Inca imperialism (A.D. 1400-1532). Among these migrants, variation in 87Sr/86Sr values suggests that individuals emigrated from geologically diverse locations, while sex differences in the migrant group include a higher percentage of females and a greater diversity in female 87Sr/86Sr values. These data, along with ethnohistoric evidence, reveal how Inca labor policies reconfigured the composition of populations in the imperial heartland. Copyright ©2009 by the Society for American Archaeology.
Keywords: dept.ant

How the Wari fashioned trophy heads for display: A distinctive modified cranium from Cuzco, Peru, and comparison to trophies from the capital region - Andrushko, V.A. (The Bioarchaeology of the Human Head: Decapitation, Decoration, and Deformation, 2011)
Keywords: dept.ant

Emics and etics of health problems in Ethiopia - Messing, S.D. (Medical Anthropology, 2011)
Keywords: dept.ant

Violence and warfare in the prehistoric San Francisco Bay area: Regional and temporal variations in conflict - Bartelink, E.J.; Andrushko, V.A.; Bellifemine, V.I.; Nechayev, I.; Jurmain, R. (The Routledge Handbook of the Bioarchaeology of Human Conflict, 2013)
The study of the origin and causes of interpersonal violence and warfare in human prehistory has drawn the interest of anthropologists for over a century (Ember and Ember 1995; Ferguson 1984; Ferguson and Whitehead 1992; Gat 2000; Haas 1990; Keeley 1996; Kelly 2000; Lambert 2002; McCall and Shields 2008; Martin and Frayer 1997; Otterbein 1994; Turney-High 1971; Walker 2001; Wrangham and Peterson 1996). Over the past few decades, a plethora of research has provided unambiguous evidence for interpersonal violence and warfare in a vast number of prehistoric societies, countering the notion of a “pacified past” (Keeley 1996; Lambert 2002; Maschner and Reedy-Maschner 1998; Milner 1995; Walker 2001). This is particularly true in California, where the notion of idyllic, peaceful hunter-gatherer groups living in a bountiful temperate climate has been contradicted by numerous skeletal studies revealing evidence of cranial trauma, projectile point injuries and trophy-taking (e.g. Andrushko et al. 2005, 2010; Jurmain 1991, 2001; Jurmain and Bellifemine 1997; Jurmain et al. 2009; Lambert 1994, 1997; Nelson 1997; Walker 1989; Wiberg 2002). The study of human skeletal remains provides a unique perspective on trauma in pastsocieties that complements evidence from material culture, site context and ethnographic and ethnohistoric accounts (Jurmain 1999; Larsen 1997; Walker 1997). While early trauma analyses focused on single case studies or small samples, more recent studies have followed a population-based perspective, with greater emphasis on the examination of trauma patterns in larger and more representative skeletal samples (e.g., Lambert 1994, 1997; Lovejoy and Heiple 1981; Steadman 2008). This population-based perspective has allowed osteologists to recognize individual, temporal and geographic variation in traumatic injuries due to a wide range of cultural, biological and environmental factors. Over the past two decades, several studies have also increasingly focused on more definitiveindicators of violence, such as cranio-facial trauma and injuries associated with embedded projectile points or other types of weaponry (e.g. Andrushko and Torres 2011; Buzon and Richman 2007; Dawson et al. 2003; Fiorato et al. 2000; Jurmain et al. 2009; Kanz andGrossschmidt 2006; Lambert 1994, 1997; Lessa and Mendonça de Souza 2004, 2006; Murphy et al. 2010; Owens 2007; Paine et al. 2007; Smith, 1996, 1997, 2003; Standen and Arriaza 2000; Steadman 2008; Torres-Rouff and Costa Junqueira 2006; Tung 2007; Walker 1989, 1997; Webb 1995; Willey and Emerson 1993). Peri-mortem mutilation, including evidence of dismemberment and trophy-taking (e.g. scalping, body part removal), is also considered a corollary to interpersonal violence and warfare practices (Andrushko et al. 2005, 2010; Lambert 2007; Steadman 2008; Tung 2007, 2008; Tung and Knudson 2008; Verano 2003). When analysed together, these direct indicators of violence – cranio-facial trauma, projectile point injury and evidence of trophy-taking – provide powerful evidence for interpersonal violence in a society. Moreover, when these indicators of conflict are analysed from a population-based perspective, as described above and employed in the present study, a more accurate and nuanced understanding of violent conflict in the past can be achieved. © 2014 Christopher Knüsel and Martin J. Smith for selection and editorial matter; individual contributions, the contributors. All rights reserved.
Keywords: dept.ant

Similarity and Diversity in the Prehistoric Colonization of Islands and Coasts by Food-Producing Communities - Leppard, T.P. (Journal of Island and Coastal Archaeology, 2014)
The colonization of the Pacific, Caribbean, and Mediterranean by food-producing communities in prehistory has rarely been considered in an explicitly comparative perspective. This article suggests that, despite evident human and environmental diversity, these insular colonization episodes have certain formal and processual similarities, especially in terms of the rate and dynamics of the colonization episodes. Specifically, in all three cases, colonizing populations seem to have rapidly crossed very great distances to find new niches, only for these events to be followed by generations of colonizing inactivity. It is proposed that such patterning may be a feature which is somehow common to episodes of coastal and insular colonization by food-producing, pre-state communities. Reasons as to why this might be-including ecological and demographic factors-are considered. This study indicates the utility of a comparative approach, and contributes to the ongoing debate centered on the extent to which insularity conditions human behavior. © 2014 Copyright Taylor & Francis Group, LLC.
Keywords: Caribbean; Mediterranean; Pacific; Pacific Ocean; coast; colonization; dept.ant; human behavior; island; islands; prehistoric

Waorani marriage - Erickson, P.I.; Beckerman, S.; Yost, J.; Diaz, R. (The Anthropology of Marriage in Lowland South America: Bending and Breaking the Rules, 2017)
Keywords: dept.ant

Sleep and social behavior in organizations: Implications for job performance - Rogers, A.P.; Budnick, C.J.; Barber, L.K. (Sleep, Personality, and Soc. Behavior, 2019)
Keywords: dept.ant

Language and economic value: A multimodal approach - McGill, K. (Language Sciences, 2022)
This article presents an approach to economic value based on the paradigm of multimodal analysis. I argue that economic value is constituted within its own interactional mode, that economic laws are constituted as semiotic resources, and that markets can ultimately be understood as the “habituation in mode” (Kress) of these resources. The article is organized as a set of problems and possible solutions for the multimodal analysis of language and value. © 2022 Elsevier Ltd
Keywords: dept.ant; peer-reviewed

Health, Diet, and Violence during Wari Expansion: Bioarchaeology at Ak’awillay, Cusco, Peru - Bey, Bridget C.; Andrushko, Valerie A.; Bélisle, Véronique (Ñawpa Pacha, 2021)
The expansion of states and empires often has important consequences for local populations, including increased violence, greater stress, or dietary modifications resulting in changing health conditions. This paper presents the analysis of 73 skeletons from the Cusco site of Ak’awillay, shedding light on diet, health, and violence in the Middle Horizon. Results indicate that the people of Ak’awillay led a rigorous lifestyle and suffered from more nutritional deficiencies compared to previous populations, possibly pointing to increased maize consumption. However, the low incidence of trauma at Ak’awillay and other Cusco sites suggest that the Wari presence in Cusco was not entrenched in violence.
Keywords: Horizonte Medio; Human remains; Middle Horizon; Wari; burials; dept.ant; diet; dieta; entierros; health; peer-reviewed; restos humanos; salud; violence; violencia

Reconstruction and analysis of the DAN5/P1 and BSN12/P1 Gona Early Pleistocene Homo fossils - Baab, Karen L.; Rogers, Michael; Bruner, Emiliano; Semaw, Sileshi (Journal of Human Evolution, 2022)
Two Early Pleistocene fossils from Gona, Ethiopia, were originally assigned to Homo erectus, and their differences in size and robusticity were attributed to either sexual dimorphism or anagenetic evolution. In the current study, we both revisit the taxonomic affinities of these fossils and assess whether morphological differences between them reflect temporal evolution or sexual variation. We generated virtual reconstructions of the mostly complete ∼1.55 Ma DAN5/P1 calvaria and the less complete 1.26 Ma BSN12/P1 fossil, allowing us to directly compare their anterior vault shapes using landmark-based shape analysis. The two fossils are similar in calvaria shape to H. erectus and also to other Early Pleistocene Homo species based on a geometric morphometric analysis of calvaria landmarks and semilandmarks. The DAN5/P1 fossil bears a particularly close affinity to the Georgian H. erectus fossils and to KNM-ER 1813 (H. habilis), probably reflecting allometric influences on vault shape. Combined with species-specific traits of the neurocranium (e.g., midline keeling, angular torus), we confirm that these fossils are likely early African H. erectus. We calculated regression-based estimates of endocranial volume for BSN12/P1 of 882–910 cm3 based on three virtual reconstructions. Although BSN12/P1 is markedly larger than DAN5/P1 (598 cm3), both fossils represent the smallest adult H. erectus known from their respective time periods in Africa. Some of the difference in endocranial volume between the two Gona fossils reflects broader species-level brain expansion from 1.77 to 0.01 Ma, confirmed here using a large sample (n = 38) of H. erectus. However, shape differences between these fossils did not reflect species-level changes to calvaria shape. Moreover, the analysis failed to recover a clear pattern of sexually patterned size or shape differences within H. erectus based on our current assessments of sex for individual fossils.
Keywords: Africa; Animals; Biological Evolution; Brain; Brain evolution; Calvaria shape; Ethiopia; Fossils; Hominidae; Homo erectus; Intraspecific variation; Pleistocene; Sexual dimorphism; Skull; anatomy and histology; animal; brain; dept.ant; evolution; fossil; hominid; human evolution; intraspecific variation; morphology; peer-reviewed; reconstruction; sexual dimorphism; skull; temporal evolution

Canine sexual dimorphism in Ardipithecus ramidus was nearly human-like. - Suwa; Sasaki, Tomohiko; Semaw, Sileshi; Rogers, Michael J.; Simpson, Scott W.; Kunimatsu, Yutaka; Nakatsukasa, Masato; Kono, Reiko T.; Zhang, Yingqi; Beyene, Yonas; Asfaw, Berhane; White, Tim D. (Proceedings of the National Academy of Sciences of the United States of America, 2021)
Body and canine size dimorphism in fossils inform sociobehavioral hypotheses on human evolution and have been of interest since Darwin’s famous reflections on the subject. Here, we assemble a large dataset of fossil canines of the human clade, including all available Ardipithecus ramidus fossils recovered from the Middle Awash and Gona research areas in Ethiopia, and systematically examine canine dimorphism through evolutionary time. In particular, we apply a Bayesian probabilistic method that reduces bias when estimating weak and moderate levels of dimorphism. Our results show that Ar. ramidus canine dimorphism was significantly weaker than in the bonobo, the least dimorphic and behaviorally least aggressive among extant great apes. Average male-to-female size ratios of the canine in Ar. ramidus are estimated as 1.06 and 1.13 in the upper and lower canines, respectively, within modern human population ranges of variation. The slightly greater magnitude of canine size dimorphism in the lower than in the upper canines of Ar. ramidus appears to be shared with early Australopithecus, suggesting that male canine reduction was initially more advanced in the behaviorally important upper canine. The available fossil evidence suggests a drastic size reduction of the male canine prior to Ar. ramidus and the earliest known members of the human clade, with little change in canine dimorphism levels thereafter. This evolutionary pattern indicates a profound behavioral shift associated with comparatively weak levels of male aggression early in human evolution, a pattern that was subsequently shared by Australopithecus and Homo. © 2021 National Academy of Sciences. All rights reserved.
Keywords: Animals; Australopithecus; Bayes Theorem; Bayes theorem; Biological Evolution; Cuspid; Ethiopia; Female; Fossils; Hominidae; Humans; Male; Models; Pan paniscus; Phylogeny; Sex Characteristics; Theoretical; adult; aggression; anatomy and histology; animal; article; canine tooth; cladistics; classification; dept.ant; evolution; female; fossil; hominid; human; male; mandibular canine; maxillary canine; nonhuman; peer-reviewed; phylogeny; sex difference; sexual characteristics; theoretical model

Estimating sexual size dimorphism in fossil species from posterior probability densities - Sasaki, Tomohiko; Semaw, Sileshi; Rogers, Michael J.; Simpson, Scott W.; Beyene, Yonas; Asfaw, Berhane; White, Tim D.; Suwa (Proceedings of the National Academy of Sciences of the United States of America, 2021)
Accurate characterization of sexual dimorphism is crucial in evolutionary biology because of its significance in understanding present and past adaptations involving reproductive and resource use strategies of species. However, inferring dimorphism in fossil assemblages is difficult, particularly with relatively low dimorphism. Commonly used methods of estimating dimorphism levels in fossils include the mean method, the binomial dimorphism index, and the coefficient of variation method. These methods have been reported to overestimate low levels of dimorphism, which is problematic when investigating issues such as canine size dimorphism in primates and its relation to reproductive strategies. Here, we introduce the posterior density peak (pdPeak) method that utilizes the Bayesian inference to provide posterior probability densities of dimorphism levels and within-sex variance. The highest posterior density point is termed the pdPeak. We investigated performance of the pdPeak method and made comparisons with the above-mentioned conventional methods via 1) computergenerated samples simulating a range of conditions and 2) application to canine crown-diameter datasets of extant known-sex anthropoids. Results showed that the pdPeak method is capable of unbiased estimates in a broader range of dimorphism levels than the other methods and uniquely provides reliable interval estimates. Although attention is required to its underestimation tendency when some of the distributional assumptions are violated, we demonstrate that the pdPeak method enables a more accurate dimorphism estimate at lower dimorphism levels than previously possible, which is important to illuminating human evolution. © 2021 National Academy of Sciences. All rights reserved.
Keywords: Animals; Bayes Theorem; Bayes theorem; Cuspid; Female; Fossils; Male; Models; Sex Characteristics; Statistical; animal; article; attention; canine tooth; controlled study; dept.ant; female; fossil; human; human experiment; intermethod comparison; male; nonhuman; peer-reviewed; primate; probability; sex difference; sexual characteristics; statistical model

Health in the Inca heartland: A paleopathological analysis of burials from the Cuzco region of Peru - Andrushko, Valerie A. (International Journal of Osteoarchaeology, 2021)
While much is known about the rise and expansion of the Inca Empire (AD 1438–1532) throughout the Andean region of South America, the health effects of the empire in its capital region remain unclear. The present study addresses the Inca Empire's impact on health in the Cuzco region of Peru through an analysis of four conditions (dental enamel hypoplasias, cribra orbitalia, porotic hyperostosis and periosteal lesions) in 929 pre-Inca and Inca burials. The study results show little change in health from the Late Intermediate Period (AD 1000–1438) to the Inca Imperial Period (AD 1438–1532). When the location of the Inca burial sites was analysed, individuals from sites closest to the centre of the empire's capital showed lower frequencies in pathological conditions compared with individuals from sites in the countryside. These results suggest that individuals centred in the Inca imperial sphere benefited from their position and experienced better health. A similar finding was also seen with the previous Wari occupation of Cuzco in the Middle Horizon (AD 600–1000), as burials within the Wari imperial sphere exhibited fewer non-specific stress indicators than those outside of it. Overall, the frequencies of pathological conditions in the Cuzco region, which ranged from 4.6% for porotic hyperostosis to 18.8% for periosteal lesions, were lower than frequencies from many coastal Peruvian sites. These differences may relate to a diverse diet provided by the Cuzco region ecosystem, as well as the absence of ecological challenges that affected coastal populations. © 2021 John Wiley & Sons, Ltd.
Keywords: dept.ant; peer-reviewed

Hybrid methods for locating and excavating early historical conflict-related domestic sites - Farley, William A.; McBride, Kevin A.; Willison, Megan K. (Historical Archaeology, 2021)
Since 2012, the Mashantucket Pequot Museum and Research Center in Mashantucket, Connecticut, in collaboration with the University of Connecticut, has carried out a research program to survey and document the battlefields of the Pequot War (1636–1637). The unique nature of the project has required the refinement of the long-standing field methods of battlefield archaeology. In this article, we argue that these techniques, while originally developed to explore sites of conflict, can be operationalized to locate 17th-century indigenous domestic sites. We describe this modified method and provide a site-specific case study to present its efficacy. © 2021, Society for Historical Archaeology.
Keywords: dept.ant; peer-reviewed

Revelations of ancient head shape: Cranial modification in the Cuzco region of Peru, Early Horizon to Inca Imperial Period - Andrushko, V.A. (American Journal of Physical Anthropology, 2021)
Objectives: Cranial vault modification (CVM), the intentional reshaping of the head, indicated group affiliation in prehistoric Andean South America. This study aims to analyze CVM data from the Cuzco region of Peru to illuminate patterns of early migration and settlement along with the later impact of the Inca Empire (AD 1438–1532) on the ethnic landscape. Materials and Methods: 419 individuals from 10 archaeological sites spanning over 2300 years were assessed for CVM using morphological analysis. Results: CVM patterns show distinct temporal attributes: the tabular type of modification appeared first and dominated the early sample (900 BC–AD 600), followed by an influx of unmodified crania during the Middle Horizon (AD 600–1000). The annular type appeared later during the Late Intermediate Period (AD 1000–1438). In the subsequent period of Inca imperialism, modification rates were higher at sites in the Cuzco countryside than in Cuzco city sites. Discussion: The study results, combined with archaeological and ethnohistoric data, reveal the sociopolitical transformations that occurred prior to and during the rise of the Inca Empire. The influx of unmodified crania during the Middle Horizon resulted at least partly from Wari occupation, while the appearance of the annular type during the LIP points to migration into the area, possibly from the Lake Titicaca region. In the Inca Imperial Period, Inca individuals at Cuzco city sites refrained from modification as a sign of their ethnic identity, while modification patterns in the Cuzco countryside likely reflect state-coerced resettlement of different ethnic groups. © 2020 Wiley Periodicals LLC.
Keywords: 15th Century; American Indian; Ancient; Archaeology; Body Modification; Female; History; Human Migration; Humans; Indians; Male; Medieval; Non-Therapeutic; Peru; Skull; South American; adult; archeology; article; body modification; controlled study; dept.ant; ethnic group; ethnology; female; history; human; human experiment; major clinical study; male; migration; occupation; pathology; peer-reviewed; skull

Review of" Indigenous Persistence in the Colonized Americas: Material & Documentary Perspectives on Entanglement" - Farley, William A. (Historical Archaeology, 2020)
Keywords: book.review; dept.ant; peer-reviewed

Language, labor and reification - McGill, Kenneth (Language Sciences, 2020)
In this article, I attempt to describe how language is reified, using the call center as an extended example. I take up recent debates regarding language and economic value, attempting to disentangle a by now substantial series of arguments about language and commodification. The theoretical core of the paper is drawn from the work of Georg Lukács, who provided the account of reification that was at the root of twentieth century critical theory. Following Lukács, I argue that what is indispensable in the process of reification is both a “contemplative stance” in relation to economic laws and the presence of “special partial systems” within the production process of commodities. These are particularly important considerations for what I refer to as the one-sided rationalization of language that occurs in call centers in particular, but also on a more widespread social basis. © 2020 Elsevier Ltd
Keywords: Commodity; Consciousness; Economic value; Language; Reification; dept.ant; peer-reviewed

Cutmarked bones from Pliocene archaeological sites at Gona, Afar, Ethiopia: implications for the function of the world's oldest stone tools - Dominguez-Rodrigo, Manuel; Pickering, Travis Rayne; Semaw, Sileshi; Rogers, Michael J (Journal of Human Evolution, 2005)
Newly recorded archaeological sites at Gona (Afar, Ethiopia) preserve both stone tools and faunal remains. These sites have also yielded the largest sample of cutmarked bones known from the time interval 2.58-2.1 million years ago (Ma). Most of the cutmarks on the Gona fauna possess obvious macroscopic (e.g., deep V-shaped cross-sections) and microscopic (e.g., internal microstriations, Herzian cones, shoulder effects) features that allow us to identify them confidently as instances of stone tool-imparted damage caused by hominid butchery. In addition, preliminary observations of the anatomical placement of cutmarks on several of the recovered bone specimens suggest that Gona hominids may have eviscerated carcasses and defleshed the fully muscled upper and intermediate limb bones of ungulates-activities that further suggest that Late Pliocene hominids may have gained early access to large mammal carcasses. These observations support the hypothesis that the earliest stone artifacts functioned primarily as butchery tools and also imply that hunting and/or aggressive scavenging of large ungulate carcasses may have been part of the behavioral repertoire of hominids by c. 2.5 Ma, although a larger sample of cutmarked bone specimens is necessary to support the latter inference. (c) 2004 Elsevier Ltd. All rights reserved.
Keywords: Africa; Carcass; Cutmarks; Defleshing/filleting; East Africa; Eastern Hemisphere; Ethiopia; Evisceration; Gona; Hominidae; Hominids; Mammalia; Pliocene; Stone tools; Sub-Saharan Africa; Ungulata; World; archaeological evidence; dept.ant; hominid; peer-reviewed; tool use

Raw material selectivity of the earliest stone toolmakers at Gona, Afar, Ethiopia - Stout, Dietrich; Quade, Jay; Semaw, Sileshi; Rogers, Michael J.; Levin, Naomi E. (Journal of Human Evolution, 2005)
Published evidence of Oldowan stone exploitation generally supports the conclusion that patterns of raw material use mere determined by local availability. This is contradicted by the results of systematic studies of raw material availability and use among the earliest known archaeological sites from Gona, Afar, Ethiopia. Artifact assemblages from six Pliocene archaeological sites were compared with six random cobble samples taken from associated conglomerates that record pene-contemporaneous raw material availability. Artifacts and cobbles were evaluated according to four variables intended to capture major elements of material quality: rock type, phenocryst percentage, average phenocryst size, and groundmass texture. Analyses of these variables provide evidence of hominid selectivity for raw material quality. These results demonstrate that raw material selectivity was a potential component of Oldowan technological organization from its earliest appearance and document a level of technological sophistication that is not always attributed to Pliocene hominids. (c) 2004 Elsevier Ltd. All rights reserved.
Keywords: Africa; Cognition; East Africa; Eastern Hemisphere; Ethiopia; Gona; Hominidae; Lithic technology; Oldowan; Pene; Pliocene; Raw materials; Sub-Saharan Africa; World; dept.ant; human activity; lithic fragment; peer-reviewed

Early Pliocene hominids from Gona, Ethiopia. - Semaw, Sileshi; Simpson, Scott; Quade, Jay; Renne, Paul; Butler, Robert; McIntosh, William; Levin, Naomi; Dominguez-Rodrigo, Manuel; Rogers, Michael (Nature, 2005)
Comparative biomolecular studies suggest that the last common ancestor of humans and chimpanzees, our closest living relatives, lived during the Late Miocene-Early Pliocene 1,2. Fossil evidence of Late Miocene-Early Pliocene hominid evolution is rare and limited to a few sites in Ethiopia 3-5, Kenya 6 and Chad 7. Here we report new Early Pliocene hominid discoveries and their palaeoenvironmental context from the fossiliferous deposits of As Duma, Gona Western Margin (GWM), Afar, Ethiopia. The hominid dental anatomy (occlusal enamel thickness, absolute and relative size of the first and second lower molar crowns, and premolar crown and radicular anatomy) indicates attribution to Ardipithecus ramidus. The combined radioisotopic and palaeomagnetic data suggest an age of between 4.51 and 4.32 million years for the hominid finds at As Duma. Diverse sources of data (sedimentology, faunal composition, ecomorphological variables and stable carbon isotopic evidence from the palaeosols and fossil tooth enamel) indicate that the Early Pliocene As Duma sediments sample a moderate rainfall woodland and woodland/grassland., (C) 2005 Nature Publishing Group
Keywords: Africa; Animals; Ardipithecus ramidus; Biodiversity; Carbon; Chad; Dental Enamel; East Africa; Eastern Hemisphere; Endomorphological variables; Environment; Ethiopia; Faunal composition; Fossils; Geographical regions; Gona; Gona Wester Margin (GWM), Afar, Ethiopia; History, Ancient; Hominidae; Jaw; Kenya; Landforms; Miocene; Pan (ape); Pan troglodytes; Pliocene; Pliocene hominids; Poaceae; Radicular anatomy; Radioisotopes; Rain; Sedimentology; Sub-Saharan Africa; Time Factors; Tooth; Trees; Upper Miocene; World; Zanclea; Zanclean; article; carbon; chimpanzee; dept.ant; enamel; evolution; fauna; forest; fossil; grassland; hominid; molar tooth; paleoenvironment; premolar tooth; priority journal; rain; sedimentology

Disparate markets: Language, nation, and education in North India - Ladousa, Chaise (American Ethnologist, 2005)
In this article, I explore the ideological underpinnings of the Indian government's language policies in the school setting, and I investigate why they fail to be compelling to residents of Banaras, a city in North India. The multiple language markets that exist in India are incommensurate and subvert the government's language policies in multiple ways. By exploring the uneven quality of these markets, this article illustrates the especially complicated dilemmas in which postcolonial nation-states are implicated.
Keywords: dept.ant

In the mouth but not on the map: visions of language and their enactment in the Hindi Belt - Ladousa, Chaise (Journal of Pragmatics, 2004)
While scholars working in colonial and post-colonial North India have devoted a great deal of attention to language variation, they have largely ignored the discursive use of names for language varieties. In this article, I investigate the ways that speakers enter into dialogic relationships with distinct voices, in the rubric of Bakhtin, depending upon which names for language varieties they mention. I reflect upon conversations between residents of Banaras, a city of approximately two million in North India, in which names for language varieties cluster into three sets. Each set of language names invokes particular language ideologies constructed in India's colonial and post-colonial past. The first two sets-one comprised by “Hindi” and “English” and the other comprised by names for more local varieties-intersect official notions about the proper fit between language and its context of use. The third set does not. In order to account for the third set, in which speakers forego official, authoritative descriptions of languages, I note that interactional phenomena, in addition to ideological dimensions of language, are crucial in understanding the ways that people differently reflect on language varieties in practice. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: Hindi; Identity; Ideology; Interaction; Metalanguage; North India; Politics; Semiotic erasure; dept.ant

Isotopic evidence for plio-pleistocene environmental change at gona, ethiopia - Levin, Naomi E; Quade, Jay; Simpson, Scott W; Semaw, Sileshi; Rogers, Michael J (Earth and Planetary Science Letters, 2004)
A 4.5 Ma record of fluvial and lacustrine deposits is well exposed at Gona, in the Afar Depression of Ethiopia. We use isotopic values of pedogenic carbonate and fossil teeth to reconstruct Plio-Pleistocene environmental change at Gona. An increase in δ13C values of pedogenic carbonates since 4.5 Ma points to a shift from woodlands to grassy woodlands in the early Pliocene, -10.4 to -3.9‰ (VPDB), to more open but still mixed environments in the late Pleistocene, -3.0 to -1.4‰ (VPDB). This pattern is also seen in isotopic records elsewhere in East Africa. However, at 1.5 Ma the higher proportion of C4 grasses at Gona is largely a result of a local facies shift to more water-limited environments. The wide range of δ13C values of pedogenic carbonate within single stratigraphic levels indicates a mosaic of vegetation for all time intervals at Gona that depends on depositional environment. Elements of this mosaic are reflected in δ13C values of both modern plants and soil organic matter and Plio-Pleistocene soil carbonate, indicating higher amounts of C4 grasses with greater distance from a river channel in both the modern and ancient Awash River systems. δ18O values of pedogenic carbonates increase up-section from -11.9‰ in the early Pliocene to -6.4‰ (VPDB) in the late Pleistocene. The wide range of δ18O values in paleovertisol carbonates from all stratigraphic levels probably reflects short-term climate changes and periods of strong evaporation throughout the record. Based on the comparison between δ18O values of Plio-Pleistocene pedogenic carbonates and modern waters, we estimate that there has been a 6.5‰ increase in mean annual δ18O values of meteoric water since 4.5 Ma. δ18O values of pedogenic carbonate from other East African records indicate a similar shift. Increasing aridity and fluctuations in the timing and source of rainfall are likely responsible for the changes in δ18O values of East African pedogenic carbonates through the Plio-Pleistocene. © 2004 Elsevier B.V. All rights reserved.
Keywords: Africa; East Africa; Ethiopia; Gona; Isotopes; Paleoclimate; Paleosols; Pleistocene; Plio-Pleistocene; Pliocene; Sub-Saharan Africa; carbonate sediment; dept.ant; isotopic analysis; paleoenvironment; peer-reviewed; sediment chemistry

Paleoenvironments of the earliest stone toolmakers, Gona, Ethiopia - Quade, Jay; Levin, Naomi E; Semaw, Sileshi; Stout, Dietrich; Renne, Paul R; Rogers, Michael J; Simpson, Scott W (Geological Society of America Bulletin, 2004)
Fluvio-lacustrine sediments of the Hadar and Busidima Formations along the northern Awash River (Ethiopia) archive almost three million years (3.4 to <0.6 Ma) of human evolution, including the earliest documented record of stone toolmaking at 2.5-2.6 Ma. This paper brings together sedimentologic and isotopic evidence for the paleoenvironmental context of early hominids from both formations, but with particular emphasis on the setting for the early toolmakers. The pre-2.92 Ma record (Hadar Formation) is characterized by low-gradient fluvial, paludal, and lacustrine deposition in an undissected topography most analogous to reaches of the modern middle Awash River near Gewane. The Gona area experienced repeated deep dissection and aggradation by the Awash River, starting between 2.92 and ca. 2.7 Ma and continuing through the top of the record at <0.6 Ma (Busidima Formation). Each aggradational succession is 10-20 m in thickness and fines upward from well-rounded conglomerates at the base to capping paleosols at the top. During this period the ancestral Awash represented by these fining upward sequences was dominantly meandering and flowed northeast, as it does today. Smaller channels tributary to the axial Awash system are also extensively exposed in the Busidima Formation. Compared to the axial-system conglomerates, the tributary channels transported finer, less mature volcanic clasts mixed with abundant carbonate nodules reworked from adjacent badlands. Stone artifacts (Oldowan; 2.6-2.0 Ma) at the oldest archaeological sites are only associated with the axial Awash system, in the bedded silts or capping paleosols of the fining upward sequences. The implements were made from rounded cobbles from the channels, but manufacture and use of the tools was always away from the channel bars, on the nearby sandy banks and silt-dominated floodplains. Archaeological sites higher in the record (Acheulian; <1.7 Ma) occur in similar axial river contexts, as well as along tributary channels further removed from artifact raw material sources. Mature paleosols in the Hadar and Busidima Formations are mostly pale to darkbrown Vertisols typified by abundant clay slickensides, pseudo-anticlinal and vertical fracturing, and carbonate nodules. Such calcic Vertisols are common in the region today, demonstrating that the paleoclimate over the past 3.4 m.y. has been semi-arid and strongly seasonal. Carbon isotopic results from pedogenic carbonates in the Vertisols allow reconstruction of the proportion of C3 plants (trees and shrubs) to C4 plants (grasses) through time. The δ 13C results from the Hadar Formation prior to 2.9 Ma range from -9.3‰ to -4.1‰, indicating a dominantly forested environment but with locally substantial (average 34%) grasses on the Awash floodplain. The δ13C values from soil carbonate in the lower Busidima Formation (2.7-1.6 Ma) increase (-6.5‰ to -2.7‰) in floodplain paleosols, indicating ∼ 50% average grass cover. Vertisols of the upper Busidima Formation (< 1.6 Ma) formed on gently sloping alluvial fans adjacent to the Awash floodplain and display even more positive δ13C values, up to -1.8‰, showing that grassland dominated the margins of the active Awash floodplain. © 2004 Geological Society of America.
Keywords: Africa; Awash; Axial flow; Carbon isotopes; Cenozoic; Deposition; Early hominids; East Africa; Eastern Hemisphere; Ethiopia; First stone tools; Gona; Human evolution; Oldowan; Paleoenvironment; Paleoenvironments; Rivers; Sediments; Sub-Saharan Africa; Tools; World; dept.ant; fluviolacustrine deposit; hominid; human activity; lithic fragment; paleoenvironment; tool use

2.6-Million-year-old stone tools and associated bones from OGS-6 and OGS-7, Gona, Afar, Ethiopia - Semaw, Sileshi; Rogers, Michael J; Quade, Jay; Renne, Paul R; Butler, Robert F; Dominguezrodrigo, Manuel; Stout, Dietrich; Hart, William S; Pickering, Travis Rayne; Simpson, Scott W (Journal of Human Evolution, 2003)
Keywords: Afar; Animalia; Bone fragments; Cutmarks; Earliest stone tools; Ethiopia; Gona; Hominidae; Mammalia; Ounda Gona; Pliocene; archaeological evidence; artifact; bone; dept.ant; peer-reviewed; tool use

Negotiating the news Indonesian press culture and power during the political crises of 1997–8 - Manzella, Joseph C (Journalism: Theory, Practice & Criticism, 2000)
Before 1998, journalists in Indonesia walked a tightrope stretched between a western ideological system that valued a free press and a system of rigid government controls. To maintain their balance, reporters and editors used strategies that were uniquely Indonesian to maintain a journalistic frame that was essentially western. This article examines those strategies in the context of the values and beliefs of print newspeople in the capital of Jakarta, focusing on news coverage of the political crises of 1997 and 1998 that culminated in the resignation of President Suharto and that unleashed a relatively free press. It contends that the contradictions and resultant conflicts between the government and newspeople in Jakarta represented a contest between western and Indonesian notions of the purposes and duties of the press. Copyright © 2000 SAGE Publications.
Keywords: Ideology of journalism; Indonesia; Occupational identity; Political change; Press; dept.ant

The new and improved clint eastwood: change and persistence in promise keepers self-help literature - Bloch, Jon P (Sociology of Religion, 2000)
Like other expressions of Christian conservatism, the Promise Keepers (PK) often enact complex and strained relationships between social change and social persistence. These strains are evident in the official PK literature, which employs techniques not unlike those used by mainstream pop psychology. These include the use of “scientific”-like classifications of information, authors presented as “experts” on the topic at hand, and the use of exercises to be enacted individually or in small PK discussion groups. Collectively, these strategies suggest that conservative Christians deal with many of the same complex role demands as non-conservatives. In Particular, the PK stance on gender roles, though Promoted as unambiguously “traditional” in favoring male leadership and female submission, in actuality often reflects acknowledgment and perhaps acceptance of some of the more egalitarian changes in gender role norms. Sociological implications and directions for future research are discussed.
Keywords: dept.ant; dept.soc

Identifying the involvement of multiple carnivore taxa with archaeological bone assemblages - Selvaggio, Marie M; Wilder, Joseph (Journal of Archaeological Science, 2001)
Information on the number of carnivore taxa that were involved with archaeological bone assemblages is pertinent to questions of site formation, hominid and carnivore competition for carcasses and the sequence of hominid and carnivore activity at sites. A majority of early archaeological bone assemblages bear evidence that both hominids and carnivores removed flesh and/or marrow from the bones. Whether flesh specialists (felids) or bone-crunchers (hyaenas), or both, fed upon the carcasses is crucial for deciphering the timing of hominid involvement with the assemblages. Here we present an initial attempt to differentiate the tooth mark signature inflicted on bones by a single carnivore species versus multiple carnivore taxa. Quantitative data on carnivore tooth pits, those resembling a tooth crown or a cusp, are presented for two characteristics: the area of the marks in millimetres, and the shape as determined by the ratio of the major axis to the minor axis of the mark. Tooth pits from bones modified by extant East African carnivores and latex impressions of tooth pits from extinct carnivore species are compared to those in the FLK Zinjanthropus bone assemblage. Data on tooth mark shape indicate greater variability in the Zinj sample than is exhibited by any individual extant or extinct carnivore species in the comparative sample. Data on tooth mark area demonstrate that bone density is related to the size of marks. Taken together, these data support the inference that felids defleshed bones in the Zinj assemblage and that hyaenas had final access to any grease or tissues that remained. © 2001 Academic Press.
Keywords: Carnivore tooth marks; Methodology; Site formation; Taphonomy; carnivore; dept.ant; dept.soc; feeding; taphonomy; tooth

The discursive construction of the german welfare state: interests and institutionality - McGill, Kenneth (Journal of Linguistic Anthropology, 2009)
This article consists of an initial theoretical attempt to describe “interests” as widespread social phenomena which emerge specifically from discursive interaction. I focus on the way in which the indexical signaling of discourse participation roles and public/private standings provide key conditions of possibility for the emergence of interests in interactional real time. The case at hand involves the German welfare state, a social institution which is constituted both on the local level of my fieldsite (a working-class suburb of the former East Berlin) and on the national level (through the popular media and through the circulation of laws, policy documents and the like). [Germany, welfare state, interests, indexical orders, institutionality].
Keywords: Germany; Indexical orders; Institutionality; Interests; Welfare state; dept.ant

The causes of porotic hyperostosis and cribra orbitalia: A reappraisal of the iron-deficiency-anemia hypothesis - Walker, Phillip L.; Bathurst, Rhonda R.; Richman, Rebecca; Gjerdrum, Thor; Andrushko, Valerie A. (American Journal of Physical Anthropology, 2009)
Porosities in the outer table of the cranial vault (porotic hyperostosis) and orbital roof (cribra orbitalia) are among the most frequent pathological lesions seen in ancient human skeletal collections. Since the 1950s, chronic iron-deficiency anemia has been widely accepted as the probable cause of both conditions. Based on this proposed etiology, bioarchaeologists use the prevalence of these conditions to infer living conditions conducive to dietary iron deficiency, iron malabsorption, and iron loss from both diarrheal disease and intestinal parasites in earlier human populations. This iron-deficiency-anemia hypothesis is inconsistent with recent hematological research that shows iron deficiency per se cannot sustain the massive red blood cell production that causes the marrow expansion responsible for these lesions. Several lines of evidence suggest that the accelerated loss and compensatory overproduction of red blood cells seen in hemolytic and megaloblastic anemias is the most likely proximate cause of porotic hyperostosis. Although cranial vault and orbital roof porosities are sometimes conflated under the term porotic hyperostosis, paleopathological and clinical evidence suggests they often have different etiologies. Reconsidering the etiology of these skeletal conditions has important implications for current interpretations of malnutrition and infectious disease in earlier human populations. Am J Phys Anthropol 139:109-125, 2009. (C) 2009 Wiley-Liss, Inc.
Keywords: Age Factors; Anemia; Archaeology; Cribra orbitalia; Fossils; History, Medieval; Humans; Hyperostosis; Nutritional Physiological Phenomena; Orbit; Paleopathology; Porosity; Porotic hyperostosis; Skull; age distribution; cribra orbitalia; dept.ant; diarrhea; erythropoiesis; fossil human; gastrointestinal infection; hemolytic anemia; human; hyperostosis; intestine parasite; iron deficiency anemia; iron intake; malnutrition; megaloblastic anemia; paleopathology; peer-reviewed; porotic hyperostosis; review

From nothing to something: the appearance and context of the earliest archaeological record - Rogers, Michael J.; Semaw, Sileshi (Sourcebook of Paleolithic Transitions: Methods, Theories, and Interpretations, 2009)
Before 2.6 million years ago (Ma), no archaeological record has been securely documented, and therefore there is no evidence of hominin tool use. Then, at 2.6–2.58 Ma, there is widespread evidence for tool manufacture and use at several archaeological sites, with undisputed stone tools and fossil fauna at Gona, Ethiopia. Additionally, the evidence from the earliest archaeological sites at Gona shows that the earliest stone tool makers were skilled flintknappers and were able to select high quality stone raw materials. The possible reasons behind this seeming abrupt transition from the absence of stone tools to the presence thereof include sampling biases, paleogeographic influences, gaps in the geological record, paleoenvironmental change, and changes in the record of hominin evolution.Based on our observations at Gona, the earliest use of flaked stone tools is likely to be slightly older than 2.6 Ma. These stone tools represent a significant change in behavior that set the stage for subsequent hominin evolution. The paleogeographic and paleoenvironmental evidence points to the earliest use of stone tools in certain settings: usually (but not always) close to raw material sources, and ecotones between riparian woodlands and open grasslands. The earliest stone tool makers were proficient, selective, and flexible in their reduction strategies. The variability we see in Pliocene artifact assemblages has much to do with different raw material sources.
Keywords: Early Stone Age; Gona; Oldowan; Paleoenvironments; Pliocene; Stone tools; dept.ant

The Oldowan-Acheulian Transition: Is there a “Developed Oldowan” Artifact Tradition? - Semaw, Sileshi; Rogers, Michael; Stout, Dietrich (Sourcebook of Paleolithic Transitions: Methods, Theories, and Interpretations, 2009)
The phrase “Developed Oldowan” (DO) was originally coined by M. Leakey to describe a technologically “advanced Oldowan” artifact tradition, that preceded the Acheulian Industry. M. Leakey further identified three stages of the DO which she labeled as the DOA, DOB and DOC. The DO (sensu lato) has been generally recognized as transitional to the Acheulian, but the status of the DOB and the DOC remains unclear. In addition to a lack of clarity in terms of classification, the DO also suffers from a lack of secure radiometric dates, even at Olduvai where it was first identified. Despite such shortcomings, archaeologists still assign assemblages into the DO, as supposedly “intermediate” or transitional between the Oldowan and the Acheulian. However, a closer look at the DO assemblages from Olduvai Gorge and other sites in Africa and the Middle East shows that the artifacts assigned into this tradition are not technologically drastically different from the preceding Oldowan. Probably the flaking characteristics of the raw material types (e.g., quartzite and limestone, and to a lesser extent basalt) and the original shape of the cobbles used by hominins may have played a major role in the final shape of the “distinctive” artifact types (such as spheroids/subspheroids) used for assigning assemblages into the DO. Further, both the DOB and the Acheulian appeared ˜1.7 million years ago (Ma) in the archaeological record, making it unlikely that the DO is a transitional artifact tradition that preceded the Acheulian. Our preliminary evaluation of the archaeological record at Gona, Ethiopia and elsewhere suggests a fairly abrupt appearance of the Acheulian after a temporally rapid transition from the Oldowan.
Keywords: Developed Oldowan; Early Acheulian; Oldowan; Oldowan-Acheulian transition; dept.ant

Pliocene animal trackways at laetoli: research and conservation potential - Musiba, Charles M.; Mabula, Audax; Selvaggio, Marie M.; Magori, Cassian C. (Ichnos-an International Journal for Plant and Animal Traces, 2008)
Laetoli, a paleoanthropological site in Northern Tanzania, is perhaps best known for its famous fossil hominid footprints that were discovered by Mary Leakey and her co-workers in 1978. The site not only preserves the hominid footprints but also trackways, which provide a snapshot of Pliocene faunal communities from East Africa and their inferred environments. Unlike the hominid footprints at site G, which have received tremendous attention, the animal trackways, especially at Localities 7, 8 and 10 have been neglected and are fast disappearing. In this paper, we discuss animal tracks at a newly discovered exposure and provide preliminary data on the tracks at this exposure and other sites. We also discuss the importance of the animal trackways as ecological indicators, which we have investigated as part of ongoing research and conservation efforts initiated by the Tanzania Field School in Paleoanthropology and the Associated Colleges of the Midwest (ACM) Tanzania Semester Abroad programs.
Keywords: Africa; Animal trackway conservation; Animal trackways; Animalia; East Africa; Hominidae; Laetoli; Paleoecology; Pliocene; Sub-Saharan Africa; Tanzania; anthropology; conference proceeding; dept.ant; footprint; hominid; paleoecology; trackway

Landscape-scale variation in hominin tool use: Evidence from the Developed Oldowan - Braun, David R.; Rogers, Michael J.; Harris, John W. K.; Walker, Steven J. (Journal of Human Evolution, 2008)
The relationship between artifact manufacture, use, and discard in the Developed Oldowan is complex. Here we use digital-image-analysis techniques to investigate the intensity of reduction in single-platform cores of the Developed Oldowan of the Okote Member, Koobi Fora Formation. Data suggest that this method provides a more accurate measure of reduction intensity than previous applications of a unifacial-scraper model. Assemblages of single-platform cores excavated from extensive lateral exposures of the Okote Member provide insights into the relationship between raw-material availability and discard patterns. Variation in reduction intensity suggests that tools are not always discarded in patterns that would be predicted by the availability of raw material. Further, it appears that hominin transport decisions involved an assessment of the potential use-life of certain forms. Many aspects of Developed Oldowan technology conform to previously developed models of curated technologies. (C) 2008 Elsevier Ltd. All rights reserved
Keywords: Curation; Hominin behavior; Landscape archaeology; Oldowan; Pleistocene; Stone Age; Stone tools; dept.ant; hominid; image analysis; peer-reviewed; tool use

Prehistoric trepanation in the Cuzco region of Peru: A view into an ancient Andean practice - Andrushko, Valerie A.; Verano, John W. (American Journal of Physical Anthropology, 2008)
In this study, patterns of prehistoric trepanation in the southern highlands of Peru were examined through an analysis of 11 Cuzco-region burial sites. Trepanations were found in 66 individuals, with several individuals exhibiting more than one trepanation, for a total of 109 perforations observed. The predominant methods used were circular cutting and scraping-methods that proved highly successful with an overall 83% survival rate and little ensuing infection. Survival rates showed a significant increase over time, apparently reflecting improvements in trepanation technique through experimentation and practical experience. Practitioners avoided certain areas of the cranium and employed methods that reduced the likelihood of damage to the cerebral meninges and venous sinuses. In many cases, trepanation as a medical treatment appears to have been prompted by cranial trauma, a finding that corroborates other studies pointing to cranial trauma as a primary motivation for the surgical procedure.
Keywords: *Skull/su [Surgery]; *Trephining/hi [History]; Cranial trauma; Culture; Cuzco; History, Ancient; Humans; Inca; Paleopathology; Peru; Skull; Skull Fractures; Skull Fractures/hi [History]; Skull Fractures/su [Surgery]; Skull/pa [Pathology]; Treatment Outcome; Trepanation; Trephining; Trephining/is [Instrumentation]; Trephining/mt [Methods]; Wounds and Injuries; Wounds and Injuries/hi [History]; Wounds and Injuries/su [Surgery]; adult; aged; article; controlled study; dept.ant; experimentation; female; head injury; human; human tissue; male; meninx; peer-reviewed; prehistoric period; school child; sinus venosus; skull; surgical technique; survival rate; trepanation

New evidence for hominin carcass processing strategies at 1.5 Ma, Koobi Fora, Kenya - Pobiner, Briana L.; Rogers, Michael J.; Monahan, Christopher M.; Harris, John W. K. (Journal of Human Evolution, 2008)
Reconstruction of early Pleistocene hominin carcass acquisition and processing behaviors are necessarily based at least in part on butchered fossil bones. This paper provides zooarchaeological and taphonomic analyses and behavioral interpretations of three similar to 1.5 million-year-old archaeofaunas from areas 1A and 103 in the Okote Member of the Koobi Fora Formation, northern Kenya: FwJj14A, FwJj14B, and GaJi14. These sites are all located in similar paleoenvironmental contexts, near shallow water with swampy, seasonally flooded areas, and some evidence for more wooded or gallery forest settings. Both individual specimen- and assemblage-level analyses of butchery-marked bones indicate that the hominins appear to have practiced similar butchery strategies at all of these sites, with butchery (defleshing, disarticulation, and marrow extraction) of both high- and low-ranked skeletal elements with no apparent preference for prey size, skeletal region, limb class, or limb portion. Only four tooth-marked specimens, including one likely crocodile-tooth-marked bone, are preserved in all three archaeofaunas. A paucity of limb epiphyses suggests that bone-crunching hyenids may have deleted these portions subsequent to hominin butchery. Strangely, there are no stone tools preserved with the 292 cut-marked and 27 percussion-marked faunal specimens (out of a total of 6,039 specimens), suggesting that raw material availability may have conditioned hominin lithic discard patterns at these locales. These assemblages increase our knowledge of the dietary behavior and ecology of Homo erectus, and provide support for variability in early Pleistocene hominin carcass foraging patterns. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Africa; Alligator; Bone modification; Butchery; Carnivory; Cut mark; Early Stone Age; East Africa; Homo erectus; Kenya; Koobi Fora; Oldowan; Percussion mark; Pleistocene; Rift Valley; Sub-Saharan Africa; Turkana; bone; carnivory; dept.ant; hominid; paleoecology; peer-reviewed; taphonomy

Cranioplasty in ancient Peru: a critical review of the evidence, and a unique case from the Cuzco area - Verano, John W; Andrushko, V A (International Journal of Osteoarchaeology, 2008)
Cranioplasty is a well-known procedure in modern neurosurgery. Although some authors have claimed it was also performed by prehistoric trepanners in various parts of the world, there is little hard evidence to support this. Here we review various claims of cranioplasty in Peru, where trepanation was widely practised in Prehispanic times. We find little support for assertions that cranioplasty was common. One recently discovered burial from the Cuzco region, however, provides the first documented case of the reinsertion of a bone plug into a trepanation opening. Copyright (C) 2008 John Wiley & Sons, Ltd.
Keywords: Cranioplasty; Peru; Trepanation; dept.ant; peer-reviewed

Quantifying variation in landscape-scale behaviors: The oldowan from Koobi Fora - Braun, D.R.; Rogers, M.J.; Harris, J.W.; Walker, S.J. (New Perspectives on Old Stones: Analyt. Approaches to Paleolithic Technol., 2010)
Studies of stone artifact morphology are beginning to rapidly increase in complexity. While these techniques provide new insights into artifact variation, it is also necessary to insure that these methods provide data that is behaviorally relevant. Here, we provide a new technique that includes three dimensional attributes to calculate platform areas to enhance the prediction of flake area from platform attributes. This data allows the calculation of more precise measures of reduction in large unifacial flake cores in Developed Oldowan assemblages (i.e., Karari Scrapers). Here, we look at measures of curation within these tool types across a landscape scale study. We apply demographic analyses of the degree to which an assemblage can be considered to be curated (i.e., the potential use life of a tool minus the actual use life of a tool). Results suggest that even though there is significant variation within a given paleogeographic setting, a higher frequency of pieces are used to their full potential in areas where raw material is predicted to have been scarce. These data suggest that hominins fulfill some aspects of a neutral model of artifact transport, yet likely make directed movements to transport tools to specific places on the ancient landscape. © 2010 Springer-Verlag New York.
Keywords: dept.ant; ⛔ No DOI found

Hominin exploitation of animal resources at the Gona Plio-Pleistocene archeological sites (Afar, Ethiopia) - Cáceres, Isabel; Rogers, Michael J.; Semaw, Sileshi; Leiss, Amanda C. (CENIEH, Centro Nacional de Investigación sobre la Evolución Humana, 2017)
Keywords: dept.ant; ⛔ No DOI found

Gona - Semaw, Sileshi; Rogers, Michael J. (The International Encyclopedia of Biological Anthropology, 2018)
Keywords: dept.ant

Fossil Cercopithecidae from the Early Pliocene Sagantole Formation at Gona, Ethiopia - Frost, Stephen R.; Simpson, Scott W.; Levin, Naomi E.; Quade, Jay; Rogers, Michael J.; Semaw, Sileshi (Journal of Human Evolution, 2020)
The Early Pliocene Sagantole Fm. in the Gona Project area, Afar State, Ethiopia, is noted for discoveries of the early hominin Ardipithecus ramidus. A large series of fossil cercopithecid primates dated to between 4.8 and 4.3 Ma has also been collected from these sediments. In this paper, we use qualitative analysis and standard dental and postcranial measures to systematically describe the craniodental remains and tentatively allocate postcrania to taxa where we are able to. We then use these data to compare these specimens to fossil assemblages from contemporary sites, interpret their paleobiology, and discuss implications for the paleoecology of the Gona Sagantole Fm. We recognize three cercopithecid species in the Gona Sagantole Fm. Pliopapio alemui makes up approximately two-thirds of the identifiable specimens; nearly all of the rest are allocated to Kuseracolobus aramisi, and a single molar indicates the presence of a second, somewhat larger but morphologically distinct papionin. Among the Early Pliocene cercopithecids from Gona are also a number of postcranial elements. None of the postcranial remains are directly associated with any of the cranial material. Nonetheless, some of the distal humeri and proximal femora can be tentatively allocated to either Pl. alemui or K. aramisi based on a combination of size, as the latter is approximately 50% larger than the former, and morphology. If these assignments are correct, they suggest K. aramisi was primarily arboreal and similar to most extant colobines, whereas Pl. alemui was more mixed in its substrate use, being more terrestrially adapted than K. aramisi, but less so than extant Papio or Theropithecus. Thus, we interpret the predominance of Pl. alemui over K. aramisi is consistent with a somewhat more open environment at Gona than at Aramis. © 2020 Elsevier Ltd
Keywords: Animals; Ardipithecus ramidus; Cercopithecidae; Ethiopia; Female; Fossils; Gona; Kuseracolobus; Life History Traits; Male; Paleobiology; Papio; Pliocene; Pliopapio; Primates; Theropithecus; anatomy and histology; animal; cranium; dentition; dept.ant; female; fossil; fossil assemblage; hominid; life history trait; male; paleobiology; paleoecology; peer-reviewed; physiology; qualitative analysis; taxonomy

Co-occurrence of Acheulian and Oldowan artifacts with Homo erectus cranial fossils from Gona, Afar, Ethiopia. - Semaw, Sileshi; Rogers, Michael J; Simpson, Scott W; Levin, Naomi E; Quade, Jay; Dunbar, Nelia; McIntosh, William C; Caceres, Isabel; Stinchcomb, Gary E; Holloway, Ralph L; Brown, Francis H; Butler, Robert F; et al. (Science advances, 2020)
Although stone tools generally co-occur with early members of the genus Homo, they are rarely found in direct association with hominins. We report that both Acheulian and Oldowan artifacts and Homo erectus crania were found in close association at 1.26 million years (Ma) ago at Busidima North (BSN12), and ca. 1.6 to 1.5 Ma ago at Dana Aoule North (DAN5) archaeological sites at Gona, Afar, Ethiopia. The BSN12 partial cranium is robust and large, while the DAN5 cranium is smaller and more gracile, suggesting that H. erectus was probably a sexually dimorphic species. The evidence from Gona shows behavioral diversity and flexibility with a lengthy and concurrent use of both stone technologies by H. erectus, confounding a simple "single species/single technology" view of early Homo. Copyright © 2020 The Authors, some rights reserved; exclusive licensee American Association for the Advancement of Science. No claim to original U.S. Government Works. Distributed under a Creative Commons Attribution NonCommercial License 4.0 (CC BY-NC).
Keywords: *Biological Evolution; *Fossils; *Hominidae; *Skull/ah [Anatomy & Histology]; Animals; Archaeological site; Behavioral diversity; Biodiversity; Biological Evolution; Co-occurrence; Ethiopia; Fossils; Hominidae; Hominidae/ah [Anatomy & Histology]; Hominidae/cl [Classification]; Hominins; Homo erectus; Humans; Paleontology; Single species; Skull; anatomy and histology; animal; classification; dept.ant; evolution; fossil; hominid; human; paleontology; peer-reviewed; skull

Technological variation in the earliest Oldowan from Gona, Afar, Ethiopia - Stout, Dietrich; Semaw, Sileshi; Rogers, Michael J.; Cauche, Dominique (Journal of Human Evolution, 2010)
Inter-site technological variation in the archaeological record is one of the richest potential sources of information about Plio-Pleistocene hominid behavior and evolution. However, appropriate methods for describing and comparing Oldowan assemblages have yet to be agreed upon, and interpretation of the early record remains highly controversial. Particularly salient is disagreement over whether the Oldowan is a single technological phenomenon or is more accurately divided into multiple regional and/or chronological traditions, perhaps including a less developed Pre-Oldowan phase in the late Pliocene. Some of this disagreement reflects theoretical and methodological differences between research traditions and some is more directly evidential. Here we present a framework for describing and interpreting Oldowan variation and apply it to three Pliocene assemblages (EG-10, EG-12, and OGS-7) from Gona, all dated to c. 2.6 million years (Ma). Results indicate proficient knapping and a full range of Oldowan reduction strategies in these earliest known occurrences, consistent with the idea of an Oldowan “technological stasis” from 2.6–1.6Ma. Patterns of variation in raw material selection and predominant reduction strategy at each site clearly indicate the importance of cultural transmission in the Oldowan, but confounding ecological and economic variation continue to render interpretation in terms of multiple tool making traditions or species inappropriate. We propose that cultural transmission and ecological adaptation should be recognized as complementary, rather than mutually exclusive, mechanisms in future attempts to explain Oldowan technological variation.
Keywords: Animals; Archaeology; Chaîne opératoire; Chi-Square Distribution; Cultural Evolution; Early Stone Age; Environment; Ethiopia; Fossils; Gona; Hominidae; Humans; Lithic technology; Paleolithic; Paleontology; Pliocene-Pleistocene boundary; Pre-Oldowan; Stone Age; Tool Use Behavior; animal; archaeological evidence; archeology; chi square distribution; cultural anthropology; cultural geography; dept.ant; dept.bio; environment; evolution; fossil; geochronology; hominid; human; paleontology; peer-reviewed; spatial variation; technological development; technology adoption; tool use

Late Miocene hominin teeth from the Gona Paleoanthropological Research Project area, Afar, Ethiopia. - Simpson, Scott W; Kleinsasser, Lynnette; Quade, Jay; Levin, Naomi E; McIntosh, William C; Dunbar, Nelia; Semaw, Sileshi; Rogers, Michael J (Journal of Human Evolution, 2015)
Since 2000, significant collections of Latest Miocene hominin fossils have been recovered from Chad, Kenya, and Ethiopia. These fossils have provided a better understanding of earliest hominin biology and context. Here, we describe five hominin teeth from two periods (ca. 5.4 Million-years-ago and ca. 6.3 Ma) that were recovered from the Adu-Asa Formation in the Gona Paleoanthropological Research Project area in the Afar, Ethiopia that we assign to either Hominina, gen. et sp. indet. or Ardipithecus kadabba. These specimens are compared with extant African ape and other Latest Miocene and Early Pliocene hominin teeth. The derived morphology of the large, non-sectorial maxillary canine and mandibular third premolar links them with later hominins and they are phenetically distinguishable and thus phyletically distinct from extant apes. Copyright © 2014 Elsevier Ltd. All rights reserved.
Keywords: *Fossils/ah [Anatomy & Histology]; *Hominidae/ah [Anatomy & Histology]; *Tooth/ah [Anatomy & Histology]; Afar; Animals; Ardipithecus; Ardipithecus kadabba; Ardipithecus ramidus; Biological Evolution; Ethiopia; Fossils; Hominidae; Hominina; Late miocene; Miocene; Orrorin; Tooth; Western ethiopian escarpment; anatomy and histology; animal; anthropology; canid; dept.ant; evolution; fossil; hominid; morphology; peer-reviewed; tooth

Political economy and language: A review of some recent literature - McGill, Kenneth (Journal of Linguistic Anthropology, 2013)
Keywords: dept.ant

The African Acheulean - Sahnouni, Mohamed; Semaw, Sileshi; Rogers, Michael (The Oxford Handbook of African Archaeology, 2013)
This article argues that the Acheulean is perhaps the longest lasting cultural–technological tradition in human history, dating from around 1.7 to 0.3 Mya and roughly corresponding to the time during which H. Erectus and H. Heidelbergensis lived in Africa. Unlike earlier Oldowan technology, Acheulean cores — handaxes, cleavers, and picks — were standardised, of predetermined shape and made on large cobbles and flakes. The extensive Acheulean archaeological record throughout Africa over 1.4 million years described is testimony to the success of this technology’s makers in different habitats, altitudes, and settings, but also to its apparent conservative cultural nature: a learned tradition passed on through thousands of generations of highly mobile hominin groups with small population sizes. Although there are differences between Early and Late Acheulean technology, the makers of these tools may have undergone more significant changes with respect to the use of other technologies, strategic land use, and social life.
Keywords: dept.ant

Discourse, organization, and the welfare state in the former east berlin - McGill, Kenneth (PoLAR: Political and Legal Anthropology Review, 2013)
In this article, I examine the statements and actions of two key informants, both of whom direct welfare programs in a district of the former East Berlin. I argue that this evidence points to a particular modality of political rationalization, which I dub organizational discourse. The entanglement of organizational discourse and governmentality are explored, as is the place of organizational discourse within both the liberal welfare state and the bygone state socialist regime.
Keywords: Discourse; Germany; Organization; Power; Welfare state; dept.ant

No magic tricks: commodity, empowerment, and the sale of StreetWise in chicago - McGill, Kenneth (Journal of Linguistic Anthropology, 2013)
Use-value and exchange-value are pragmatic features of commodity exchange which are apparent from the careful study of specific interactions, as well as from the viewpoint of economic processes at large. While Marx's well-known attempt to describe this pair of concepts in Capital (2001) takes the latter tack, I attempt here to take the formeri.e., to approach the composition of the commodity from the point of view of the pragmatics of interaction. In doing so, I offer a semiotic model of the valuation of commodities which differs from accounts given by Kockelman (2006) and Agha (2011). The ethnographic object at stake in this essay is StreetWise, a Chicago street newspaper said to have empowering effects on its vendors.
Keywords: Commodity; Empowerment; Street newspapers; United States; Value; dept.ant

Investigating a child sacrifice event from the Inca heartland - Andrushko, Valerie A.; Buzon, Michele R.; Gibaja, Arminda M.; McEwan, Gordon F.; Simonetti, Antonio; Creaser, Robert A. (Journal of Archaeological Science, 2011)
Human sacrifice in the Inca Empire at times took the form of the capacocha, a sacrificial rite involving the most beautiful children in the empire. In this study, we investigate a possible capacocha at the pre-Columbian site of Choquepukio in the Cuzco Valley of Peru. During excavations at Choquepukio in 2004, seven children (aged 3-12 years) were discovered buried together; accompanying them was an elaborate assemblage of high status artifacts similar to those from other recent archaeological finds that are believed to be capacocha sacrifices. Since colonial documents indicate that capacocha children were selected from diverse regions of the empire, we initiated a radiogenic strontium isotope analysis to determine the origins of the children found at Choquepukio. Our analysis showed that, indeed, two children in the assemblage had non-local origins. When considered together, the osteological, archaeological, and isotopic evidence suggest that a capacocha event occurred at Choquepukio, representing the only lower-elevation capacocha to have been found in the Cuzco region. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Andes; Bioarchaeology; Capacocha; Cuzco; Strontium isotope analysis; archaeological evidence; archaeology; artifact; dept.ant; isotopic analysis; strontium isotope

Skeletal evidence for Inca warfare from the Cuzco region of Peru - Andrushko, Valerie A; Torres, Elva C (American Journal of Physical Anthropology, 2011)
This article addresses the bioarchaeological evidence for Inca warfare through an analysis of 454 adult skeletons from 11 sites in the Inca capital region of Cuzco, Peru. These 11 sites span almost 1000 years (AD 600-1532), which allows for a comparison of the evidence for warfare before the Inca came to power (Middle Horizon AD 600-1000), during the time of Inca ascendency in the Late Intermediate Period (AD 1000-1400), and after the Inca came to power and expanded throughout the Cuzco region and beyond (Inca Imperial Period, AD 1400-1532). The results indicate that 100 of 454 adults (22.0%) showed evidence of cranial trauma. Of these, 23 individuals had major cranial injuries suggestive of warfare, consisting of large, complete, and/or perimortem fractures. There was scant evidence for major injuries during the Middle Horizon (2.8%, 1/36) and Late Intermediate Period (2.5%, 5/199), suggesting that warfare was not prevalent in the Cuzco region before and during the Inca rise to power. Only in the Inca Imperial Period was there a significant rise in major injuries suggestive of warfare (7.8%, 17/219). Despite the significant increase in Inca times, the evidence for major cranial injuries was only sporadically distributed at Cuzco periphery sites and was entirely absent at Cuzco core sites. These findings suggest that while the Inca used warfare as a mechanism for expansion in the Cuzco region, it was only one part of a complex expansion strategy that included economic, political, and ideological means to gain and maintain control. Copyright © 2011 Wiley-Liss, Inc.
Keywords: *Archaeology; *Skull/in [Injuries]; *Warfare; Adolescent; Adult; Archaeology; Female; History, 15th Century; History, Medieval; Humans; Male; Middle Aged; Peru; Skull; War; Weapons; adult; archeology; article; battle injury; bioarchaeology; bone injury; conflict; dept.ant; history; human; imperialism; major clinical study; peer-reviewed; politics; skeletal injury; skeleton; skull injury; trauma; war; weapon

Partnerships, pitfalls, and ethical concerns in international bioarchaeology - Turner, Bethany L; Andrushko, Valerie A (Social Bioarchaeology, 2011)
Keywords: Culturally affiliated descent communities and bioarchaeologists - connections to human remains; Ethical issues, studying human remains - training students in bioarchaeology in united states; Ethical practice, central to bioarchaeology in united states - component of training in the field; Ethics and bioarchaeology in united states - issues of ethical practice in excavation; Human remains analyses - valuable bridges, between past and present; Language barriers and convoluted online submission processes - and additional obstacles; Non-destructive analyses - toward ethical practice in peruvian bioarchaeology; Partnerships, pitfalls and ethical concerns - in international bioarchaeology; Passage of NAGPRA - the native american graves protection and repatriation act of 1990; Practice of bioarchaeology in peru - influenced by cultural and political economic processes; dept.ant

Trophy-taking and dismemberment as warfare strategies in prehistoric central California. - Andrushko, Valerie A; Schwitalla, Al W; Walker, Phillip L (American Journal of Physical Anthropology, 2010)
We document evidence for trophy-taking and dismemberment with a new bioarchaeological database featuring 13,453 individuals from prehistoric central California sites. Our study reveals 76 individuals with perimortem removal of body parts consistent with trophy-taking or dismemberment; nine of these individuals display multiple types of trophy-taking and dismemberment for a total of 87 cases. Cases span almost 5,000 years, from the Early Period (3000-500 BC) to the Late Period (AD 900-1700). Collectively, these individuals share traits that distinguish them from the rest of the population: a high frequency of young adult males, an increased frequency of associated trauma, and a tendency towards multiple burials and haphazard burial positions. Eight examples of human bone artifacts were also found that appear related to trophy-taking. These characteristics suggest that trophy-taking and dismemberment were an important part of the warfare practices of central Californian tribes. Temporally, the two practices soared in the Early/Middle Transition Period (500-200 BC), which may have reflected a more complex sociopolitical system that encouraged the use of trophies for status acquisition, as well as the migration of outside groups that resulted in intensified conflict. Overall, trophy-taking and dismemberment appear to have been the product of the social geography of prehistoric central California, where culturally differentiated tribes lived in close proximity to their enemies.
Keywords: *Corpse Dismemberment/hi [History]; *Fossils; *Social Behavior; Bioarchaeology; California; Corpse Dismemberment; Cutmarks; Fossils; History, Ancient; Humans; Male; Native American; Social Behavior; Trauma; United States; Violence; War; Warfare; article; artifact; autopsy; dept.ant; ethnic group; ethnicity; female; geography; human; injury; major clinical study; male; migration; peer-reviewed; physical anthropology; posthumous care

The bioarchaeology of Wari collapse in Cuzco, Peru: A study of health and trauma from the Middle Horizon-Late Intermediate Period transition at Cotocotuyoc - Andrushko, Valerie (The Wari Civilization and Their Descendants: Imperial Transformation in Pre-Inca Cuzco, 2020)
Drawing on research conducted in Cuzco, Peru, The Wari Civilization and Their Descendants: Imperial Transformation in Pre-Inca Cuzco, Peru analyzes the political and social transformations that led to the downfall of the Wari civilization in the Andean Middle Horizon period (AD 500–1000) and resulted in the rise of the Inca state. The contributors to this collection present evidence of the Wari civilization’s robust, imperialistic occupation of Cuzco, and argue that this presence laid the groundwork for later regional polities that can be traced to the Late Horizon Inca period (AD 1476–1532). This collection fills a gap in scholarly literature on Cuzco prehistory, the provincial southern highlands of the Wari civilization, and early imperialism in the Andes.
Keywords: dept.ant

Ontology, belief and the politics of sanction: An application of Badiou’s Theory of the Event - McGill, Kenneth (Anthropological Theory, 2019)
In this article, I apply Alain Badiou's theory of the event to make sense of the beliefs of an anti-sanction activist in Germany. Sanctions are deductions to unemployment benefits imposed by jobs counselors on their unemployed clients. Ethnographic research with Renate shows how her beliefs about the welfare state and her own personal life are examined by her as conditions for the abolition of sanctions in Germany, which is considered here as an event within Badiou’s ontological framework.
Keywords: Badiou; Germany; activism; dept.ant; event; mourning; peer-reviewed; sanctions; welfare state

A quantitative dwelling-scale approach to the social implications of maize horticulture in New England - Farley, William A.; Fox, Amy N.; Hrynick, M. Gabriel (American Antiquity, 2019)
We compare domestic architectural features in New England and the Maritime Peninsula to investigate the relationship between the adoption of horticulture and its relationship to social and settlement change during the Woodland Period. Horticulture was not practiced on the Maritime Peninsula until after European contact, despite cultural and environmental similarity to New England. In New England, horticulture has been implicated in profound social and settlement changes. However, aggregated villages, a unit typically investigated for evidence of social change, have proven elusive in the archaeological record. We compiled and analyzed a dataset of dwelling features instead of relying on identifiable villages. This novel quantitative approach uses dwelling feature shape and size as a proxy for social and settlement change, considering these changes at the scale of the house. We find that, during the Woodland Period, dwelling size was overall slightly larger in New England than on the Maritime Peninsula, but ranges heavily overlapped. After the introduction of horticulture, however, dwellings in New England grew in size overall and assumed bimodally distinct larger and smaller forms, which likely necessitated a restructuring of social and economic behavior. This pattern correlates maize horticulture with changes in social and economic lifestyle in Late Woodland New England. , Nous comparons des structures d'habitation domestiques de sites archéologiques de la Nouvelle-Angleterre et de la péninsule maritime afin d'explorer les conséquences de l'adoption généralisée de l'horticulture en termes de changements sociaux et de transformation des modes d’établissement en Nouvelle-Angleterre à la période Sylvicole. L'horticulture ne fut pas pratiquée dans la péninsule maritime avant la période du contact européen, malgré de fortes similarités culturelles et environnementales avec la Nouvelle-Angleterre. En Nouvelle-Angleterre, l'horticulture est présentée comme ayant été la source de changements sociaux profonds et d'une transformation des modes d’établissement. Au niveau archéologique cependant les sites de village font défaut, alors qu'ils constituent habituellement un repère pour l'identification et l’étude des changements sociaux; cette situation a provoqué des débats sur l'impact socio-économique de l'horticulture. Nous analysons ici un ensemble de données concernant des structures d'habitation individuelles en faisant fi de l'idée selon laquelle l’étude d'un village bien défini est nécessaire. Cette approche quantitative novatrice nous permet d'aborder la question des changements sociaux et de l’évolution des modes d’établissement à l’échelle de l'habitation, par l'intermédiaire de la forme et des dimensions des structures. Nous observons que durant la période sylvicole la taille des structures d'habitation était en général légèrement plus grande en Nouvelle-Angleterre que dans la péninsule maritime, malgré une fourchette de dimensions comparable pour les deux régions. Les habitations de la Nouvelle-Angleterre voient toutefois leur taille augmenter après l'introduction de l'horticulture, alors que se développe une division bimodale entre de grandes et de petites structures, changements rendus possibles par une probable réorganisation des comportements économiques et sociaux. Cette tendance met en corrélation la culture du maïs avec une transformation des modes de vie économiques et sociaux en Nouvelle-Angleterre durant le sylvicole supérieur.
Keywords: Maritime Peninsula; Native American; New England; Woodland; architecture; dept.ant; horticulture; maize; nonparametric analysis; peer-reviewed; sedentism; village

Ardipithecus ramidus postcrania from the Gona Project area, Afar Regional State, Ethiopia. - Simpson, Scott W; Levin, Naomi E; Quade, Jay; Rogers, Michael J; Semaw, Sileshi (Journal of human evolution, 2019)
Functional analyses of the 4.4 Ma hominin Ardipithecus ramidus postcrania revealed a previously unknown and unpredicted locomotor pattern combining arboreal clambering and a form of terrestrial bipedality. To date, all of the fossil evidence of Ar. ramidus locomotion has been collected from the Aramis area of the Middle Awash Research Project in Ethiopia. Here, we present the results of an analysis of additional early Pliocene Ar. ramidus fossils from the Gona Project study area, Ethiopia, that includes a fragmentary but informative partial skeleton (GWM67/P2) and additional isolated manual remains. While we reinforce the original functional interpretations of Ar. ramidus of having a mixed locomotor adaptation of terrestrial bipedality and arboreal clambering, we broaden our understanding of the nature of its locomotor pattern by documenting better the function of the hip, ankle, and foot. The newly recovered fossils document a greater adaptation to bipedality in the Ar. ramidus ankle and hallux than previously recognized. In addition, a newly discovered scaphoid bone with a fusing os centrale provides further evidence about the nature of hominin hand evolution. Copyright © 2018 Elsevier Ltd. All rights reserved.
Keywords: *Fossils/ah [Anatomy & Histology]; *Hominidae/ah [Anatomy & Histology]; *Hominidae/ph [Physiology]; *Locomotion; Adaptation, Biological; Afar; Animals; Ardipithecus ramidus; Biological Evolution; Bipedality; Ethiopia; Fossils; Gona; Hominidae; Hominin; Locomotion; Pliocene; Postcrania; Skeleton; Skeleton/ah [Anatomy & Histology]; adaptation; anatomy and histology; animal; bipedalism; bone; cranium; dept.ant; evolution; fossil; hominid; locomotion; paleontology; peer-reviewed; physiology; skeleton

Archaeology and the origins of human cumulative culture: a case study from the earliest Oldowan at Gona, Ethiopia - Stout, Dietrich; Rogers, Michael J.; Jaeggi, Adrian V.; Semaw, Sileshi (Current Anthropology, 2019)
The capacity of Homo sapiens for the intergenerational accumulation of complex technologies, practices, and beliefs is central to contemporary accounts of human distinctiveness. However, the actual antiquity and evolutionary origins of cumulative culture are not known. Here we propose and exemplify a research program for studying the origins of cumulative culture using archaeological evidence. Our stepwise approach disentangles assessment of the observed fidelity of behavior reproduction from inferences regarding required learning mechanisms (e.g., teaching, imitation) and the explanation of larger-scale patterns of change. It is empirically grounded in technological analysis of artifact assemblages using well-validated experimental models. We demonstrate with a case study using a toolmaking replication experiment to assess evidence of behavior copying across three 2.6 Ma Oldowan sites from Gona, Ethiopia. Results fail to reveal any effects of raw material size, shape, quality, or reduction intensity that could explain the observed details of intersite technological variation in terms of individual learning across different local conditions. This supports the view that relatively detailed copying of toolmaking methods was already a feature of Oldowan technological reproduction at ca. 2.6 Ma. We conclude with a discussion of prospects and implications for further research on the evolution of human cumulative culture.
Keywords: dept.ant; peer-reviewed

The first technical sequences in human evolution from East Gona, Afar region, Ethiopia - de Lumley, Henry; Barsky, Deborah; Moncel, Marie Hélène; Carbonell, Eudald; Cauche, Dominique; Celiberti, Vincenzo; Notter, Olivier; Pleurdeau, David; Hong, Mi-Young; Rogers, Michael J.; Semaw, Sileshi (Antiquity, 2018)
Gona in the Afar region of Ethiopia has yielded the earliest Oldowan stone tools in the world. Artefacts from the East Gona (EG) 10 site date back 2.6 million years. Analysis of the lithic assemblage from EG 10 reveals the earliest-known evidence for refitting and conjoining stone artefacts. This new information supplements data from other Oldowan sites in East Africa, and provides an important insight into the technological capacities and evolutionary development of hominins during this period.
Keywords: East Gona; Ethiopia; Oldowan; dept.ant; knapping; peer-reviewed; refitting

The Early Acheulean ~1.6–1.2 Ma from Gona, Ethiopia: Issues related to the emergence of the Acheulean in Africa - Semaw, Sileshi; Rogers, Michael J.; Cáceres, Isabel; Stout, Dietrich; Leiss, Amanda C. (The Emergence of the Acheulean in East Africa and Beyond: Contributions in Honor of Jean Chavaillon, 2018)
Konso in Ethiopia and Kokiselei in Kenya, both dated to ~1.7 million years ago (Ma), and FLK West, a recently reported site from Olduvai dated to 1.7 Ma, are the earliest Acheulean sites known in East Africa. Ongoing archaeological investigations at Gona, in the Afar Depression of Ethiopia, have also produced early Acheulean stone assemblages at several sites, estimated to ~1.6–1.2 Ma. A number of sites, including BSN-12 and OGS-12, have yielded archaeological materials comparable to the earliest Konso artifacts. The stone assemblages from the Gona sites consist of crudely made handaxes, cleavers, and picks, as well as Mode I (Oldowan) cores, and débitage. A variety of raw materials were exploited at Gona, with trachyte, rhyolite, and basalt being the most common.Our understanding of the behavioral and ecological background for the emergence of the Acheulean is still limited. Preliminary comparisons of BSN-12 and OGS-12 with other early Acheulean sites demonstrate variability in paleoecological settings as well as raw material use. Current archaeological evidence indicates that early Homo erectus/ergaster use of this new technology was already in place in East Africa ~1.75 Ma. At Gona and elsewhere in Africa, continued survey and excavations are needed to document sites with potential for yielding archaeological traces that will help our understanding of the Oldowan–Acheulean transition, the identity of the toolmakers, and the function of the early Acheulean Large Cutting Tools (LCTs).
Keywords: Ethiopia; Gona; Oldowan–Acheulean transition; Technical behaviors; dept.ant

“Tangled up in these conceptualities”: Sanction, protest, and ideology in Berlin, Germany - McGill, Kenneth (American Anthropologist, 2017)
This article examines one informant's approach to the relationship between ideological concepts and political power. I argue that ideological representation must be understood on its own terms, rather than within a larger theory of discourse. I point toward three key qualities of every encounter with ideological representation: subjectivity, discontinuity, and commitment. The fieldwork on which this article is based occurred in Berlin, Germany, during the fall 2014. During this period, my research focused on activists committed to overturning the sanctioning policy (Sanktionspolitik), which allows case managers to dock the unemployment benefits of their clients. [ideology, subjectivity, welfare state, Germany]
Keywords: dept.ant